La concepción de “alma bella” en “El Espíritu del Cristianismo y su Destino”.: Su relación con la noción homónima esbozada por Friedrich Schiller (Revista Eletrônica Estudos Hegelianos, 2022)
This paper is about the notion of ‘beautiful soul’ in The Spirit of Christianity and its Fate: an unpublished article, written by Hegel in year 1798. The purpose of this paper is to show that the Hegelian definition of the beautiful subjectivity is similar to Schiller’s own notion. Secondly, the intended goal is to demonstrate that Hegel has a critical perspective on Schiller’s notion of beauty of soul. In other words, Hegel objects Schiller’s view of beauty of soul as an ideal. Thirdly, I will analyze the grounds of the theoretical disagreement between both thinkers. Finally, I will explain why Hegel choose Jesus as the main example of his critical notion of ‘beautiful soul’.